Habitat Types Effect on Diversity, Distribution and Abundance of Dung Beetles: Dung Beetles Diversity in Different Habitats (Biological Sciences - PJSIR, 2021)
Dung beetles are ecologically important taxa to study the assessment of habitat modification and disturbance across the globe. This study was aimed to explore community composition, species richness and abundance of dung beetles in response to Gujrat, Punjab, Pakistan. Dung beetle assemblage were sampled from four habitat (natural rangeland, cropland, roadside and housing colonies) during 2014-2016 by placing pitfall traps baited with cattle dung. A total number of 540 specimens representing 17 species belonging to seven genera and four tribes were collected. We calculated species relative abundance in natural habitat (34.8%), cropland habitat (40.4%) and in road side areas (25.2%) was recorded, whereas no specimens were recorded in urban areas. Aphodius contaminatus (42.96%) was the most abundant species followed by Onitis castaneous (26.29%) and Onitis singhalensis (20.74%). Tunnellers (50.58%) and dwellers (49.01%) were dominant in all habitats, whereas rollers were least abundant (1.37%). The values of Shannon-Wiener (H) diversity and evenness (E) showed variations among different habitats i.e. natural habitat (H=1.20; E=0.55), cropland habitat (H=1.41, E=0.32) and roads-side (H=0.80, E=0.37). The study showed that cropland served as a major habitat for dung beetles due to its uniformity and close association with mammalian fauna. The results emphasized that natural habitats within the agro-ecosystem have become isolated and fragmented habitat with lesser stability and low resources thus resulting into less diverse habitat. Roadside areas are in close proximity with cropland and act as corridors for efficient species flow within ecosystem due to cattle movement through these areas.